2016
DOI: 10.1016/j.annemergmed.2015.07.495
|View full text |Cite
|
Sign up to set email alerts
|

Diphenhydramine as Adjuvant Therapy for Acute Migraine: An Emergency Department–Based Randomized Clinical Trial

Abstract: Background More than one million patients present to US emergency departments (ED) annually seeking care for acute migraine. Parenteral anti-histamines have long been used in combination with anti-dopaminergics such as metoclopramide to treat acute migraine in the ED. High quality data supporting this practice do not exist. We determined whether administration of diphenhydramine 50mg IV + metoclopramide 10mg IV resulted in greater rates of sustained headache relief than placebo+ metoclopramide 10mg IV. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 24 publications
1
39
0
1
Order By: Relevance
“…We identified one study of diphenhydramine for migraine . In a class 1 study, there were no differences in outcomes or adverse events among 208 adults randomized to diphenhydramine 50 mg IV or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…We identified one study of diphenhydramine for migraine . In a class 1 study, there were no differences in outcomes or adverse events among 208 adults randomized to diphenhydramine 50 mg IV or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Literature has shown that a drop-out rate of less than 5% is minor,26 27 and the calculated ratios of dropped participants to total events (3/34 and 7/15, respectively) were not significant to influence intervention effect. High risk for bias was noted for the ‘Other bias’ category in the Friedman et al (2016) study as the trial was halted slightly past the halfway point due to enforcement of a stopping rule 24. This stopping rule was established prior to initiation of the trial and stated that the study was to be stopped if the absolute risk reduction of headache was less than 7.5% in the cohort receiving diphenhydramine and metoclopramide.…”
Section: Resultsmentioning
confidence: 99%
“…Only four RCTs satisfied eligibility criteria and sample sizes were small. One study was halted near the halfway point due to enforcement of a stopping rule, introducing the possibility that results may not reflect the actual outcome if the study was completed 24. In addition, a no-intention-to-treat analysis was performed for drop-outs.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyzine possesses anxiolytic qualities and has been studied for use in pain alone and with DHE in migraine . Diphenhydramine is frequently used as a parenteral adjunct for migraine treatment in the ED, though study results have been mixed . Neither drug is listed in the AHS guidelines or the 2000 AAN practice parameter.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Diphenhydramine is frequently used as a parenteral adjunct for migraine treatment in the ED, though study results have been mixed. 11,[20][21][22][23][24] Neither drug is listed in the AHS guidelines or the 2000 AAN practice parameter.…”
Section: Introductionmentioning
confidence: 99%